Mesenchymal Stromal Cell Therapy in Spinal Cord Injury: Mechanisms and Prospects - Xie, Ji-Le; Wang, Xing-Ran; Li, Mei-Mei; Tao, Zi-Han; Teng, Wen-Wen; Saijilafu, (Frontiers in Cellular Neuroscience, 2022)
Spinal cord injury (SCI) often leads to severe motor, sensory, and autonomic dysfunction in patients and imposes a huge economic cost to individuals and society. Due to its complicated pathophysiological mechanism, there is not yet an optimal treatment available for SCI. Mesenchymal stromal cells (MSCs) are promising candidate transplant cells for use in SCI treatment. The multipotency of MSCs, as well as their rich nutritional and immunomodulatory abilities through paracrine signaling, are expected to play an important role in neural repair. At the same time, the simplicity of MSCs isolation and culture and the bypassing of ethical barriers to stem cell transplantation make them more attractive. However, the MSCs concept has evolved in a specific research context to encompass different populations of cells with a variety of biological characteristics, and failure to understand this can undermine the quality of research in the field. Here, we review the development of the concept of MSCs in order to clarify misconceptions and discuss the controversy in MSCs neural differentiation. We also summarize a potential role of MSCs in SCI treatment, including their migration and nutritional and immunomodulatory effects, and their ability to relieve neuropathic pain, and we also highlight directions for future research.